Options to overcome worm infection in small ruminants for producers in Nepal - Bain, R.K.; Joshi, B.R.; Gauchan, D.; Gray, G.D. (Australian Centre for International Agricultural Research, 2004)
The paper begins with Nepals geographic location, climate, altitude, area in sq km., regions, and economy. This is followed by livelihood analysis and poverty focus referring to capital access and vulnerability content. Then the paper examines the role of small ruminants in the countrys economy. Sedentary goat production in the hill districts with ref to farming systems, livestock management, animal health issues, helminth problems. Options for helminth control are discussed in the following section. The paper then presents two case studies, viz, sedentary system case study - Pyughar Village, and transhumance system case study - Ghandruk village. These are discussed with regard to constraints to goat production, symptoms and seasonality of disease, and disease management. The last topic of discussion is transhumance sheep and goat production in the mountain districts. In this section, farming systems, livestock management, animal health issues, and helminth problems are highlighted.